Shelf-Life Prediction of Shallot Powder Using Accelerated Shelf-Life Testing (ASLT) Method by the Arrhenius Equation Approach - Permatasari, Niken Ayu; Hardiyanti, Indah; Suryani, Ani; Yuliasih, Indah (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2022)
AbstractThe storage process of shallot powder can cause a quality decrease. This study aims to estimate shelf-life of shallot powder at various storage temperatures and determine quality changes during storage. This study used a Completely Randomized Design with two factors to determine quality changes of shallot powder, i.e. the coating and storage temperature. The statistical analysis results showed that the coating, storage temperature, and interaction between the two factors affected Volatile Reducing Substances (VRS) levels. The two factors and their interaction do not influence the water content. Shelf-life estimation was performed using the Arrhenius method. Coated shallot powder has a longer shelf-life than uncoated shallot powder. Shelf-life determination was performed based on water content parameters. The shelf-life of uncoated shallot powder was 337 days at 30 °C, 322 days at 40 °C, and 309 days at 50 °C. The shelf-life of coated shallot powder was 353 days at 30 °C, 340 days at 40 °C, and 328 days at 50 °C. The coating process can extend the shelf-life of shallot powder.Keywords: Accelerate Shelf-Life Testing (ASLT), Arrhenius, coating, shallot powder AbstrakProses penyimpanan dapat menyebabkan penurunan mutu bawang merah bubuk. Penelitian ini bertujuan untuk menduga umur simpan produk bawang merah bubuk pada berbagai suhu penyimpanan dan mengetahui perubahan mutunya selama penyimpanan. Penelitian ini menggunakan Rancangan Acak Lengkap dengan dua faktor untuk mengetahui perubahan mutu bawang merah bubuk, yaitu penggunaan penyalut dan suhu penyimpanan. Hasil analisis statistik menunjukkan bahwa penyalutan, suhu penyimpanan, dan interaksi antara kedua faktor memengaruhi kadar Volatile Reducing Substance (VRS). Kadar air tidak dipengaruhi oleh kedua faktor dan interaksi antara kedua faktor tersebut. Pendugaan umur simpan dilakukan menggunakan metode Arrhenius. Bubuk bawang merah dengan proses penyalutan memiliki umur simpan yang lebih lama dibandingkan bubuk bawang merah tanpa proses penyalutan. Penentuan umur simpan dilakukan berdasarkan parameter kadar air, Umur simpan bawang merah bubuk tanpa penyalutan adalah 337 hari pada suhu 30 °C, 322 hari pada suhu 40 °C, dan 309 hari pada 50 °C. Umur simpan bawang merah bubuk dengan penyalutan adalah 353 hari pada suhu 30 °C, 340 hari pada suhu 40 °C, dan 328 hari pada suhu 50 °C. Proses penyalutan mampu memperpanjang umur simpan bawang merah bubuk.Kata kunci: Accelerate Shelf-Life Testing (ASLT), Arrhenius, bawang merah bubuk, penyalutan